A Meeting of Minds: In Recognition of the Contributions of Randall J. Cohrs - Grose, Charles; Mahalingam, Ravi; Rovnak, Joel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
A Special Issue in memory of Randall J. Cohrs, Ph.D. Topics include original research reports on a variety of viruses as well as reviews and commentaries on Randy's contributions to many investigations.